Phylogenetic analysis and genetic evolution of porcine respiratory coronavirus in Guangxi province, Southern China from 2022 to 2024 - Shi, Yuwen; Shi, Kaichuang; Yin, Yanwen; Feng, Shuping; Long, Feng; Lu, Wenjun; Qu, Sujie; Ma, Yan; He, Jiakang (Frontiers in Microbiology, 2025)
Porcine respiratory coronavirus (PRCV) is an important coronavirus to cause respiratory syndrome in pigs. To analyze the genetic and evolutional characteristics of PRCV in Guangxi province, southern China, a total of 6,267 clinical samples were collected from different pig farms, harmless treatment plants and abattoirs in Guangxi province during 2022–2024. Seventeen positive samples of PRCV were selected to amplify and analyze the S, M, and N gene sequences. The results showed that the positivity rate of PRCV was 1.13% (71/6,267) using RT-qPCR. The homology analysis revealed that the nucleotide (amino acid) identity were 98.2–100% (96.6–100%) among the obtained 17 S, M, and N gene sequences, and 91.3–98.1% (88.8–98.0%) among the obtained strains and the reference strains from different countries. The phylogenetic analysis indicated that all PRCV strains could be divided into two groups, tentatively designated group I and group II, and each group was further divided into different clades. The strains obtained from Guangxi province distributed in group I, and formed an independent clade. They were most closely related to PRCV 137 isolate 86/135308 strain from the United Kingdom basing on the S, M, and N gene sequences. The sequence analysis revealed that all PRCV strains from Guangxi province obtained in this study showed 672 nt/224 aa deletion in the 5′ region of S gene, and there existed 37 amino acid mutations in different regions in S gene of different PCRV strains. Recombination analysis of S gene sequences did not find any recombination event. The Bayesian analysis indicated that all PRCV strains could be divided into Group I and II, and the obtained Guangxi strains belonged to group I. The population size of circulating PRCV strains kept slightly upward trend since its discovery in 1984 until 2010, showed a steady downward trend until 2020, and then a slight increase. The results suggested that the PRCV strains circulating in Guangxi province originated from Europe, and have evolved independently with genetic diversity. These findings enriched the epidemiological data of PRCV, and provided new information on the prevalence and genetic evolution of PRCV in Guangxi province of China.